THE IMPLEMENTATION OF THE TASMI’ METHOD IN IMPROVING THE QUALITY OF QUR’ANIC MEMORIZATION AMONG TAHFIDZ PROGRAM STUDENTS AT MADRASAH IBTIDAIYAH - Muzayadatus Rohma, Rossa; Ali Mahsun (PGMI UNHASY, 2026)
This study aims to describe the implementation of the tasmi’ method in improving the quality of Qur’anic memorization among tahfidz program students at Madrasah Ibtidaiyah. This study employed a qualitative approach with a case study design. The research subjects consisted of tahfidz teachers and tahfidz program students at MIN 3 Jombang selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that the implementation of the tasmi’ method was carried out through routine memorization recitation activities in front of teachers and peers, accompanied by repetition and direct feedback on recitation errors. The tasmi’ method contributed to improving students’ memorization quality, particularly in terms of fluency, tajwid accuracy, makharijul huruf mastery, and consistency of recitation. In addition, the method encouraged students to become more disciplined, confident, and active in tahfidz learning activities. However, the implementation of the tasmi’ method still encountered several challenges, such as differences in students’ basic abilities and limited instructional time. This study concludes that the tasmi’ method is an effective pedagogical strategy in supporting the improvement of Qur’anic memorization quality among Madrasah Ibtidaiyah students through active, collaborative, and sustainable learning processes.